Seismic soil-foundation-structure interaction analysis of ventilation stack - Jaya, V.; Dodagoudar, G. R.; Boominathan, A. (Journal of Structural Engineering, 2025)
Soil-foundation-structure interaction (SFSI) analysis of a ventilation stack located in a nuclear power plant site is presented in this paper. Structures of this type are highly sensitive to seismic loads, as the tuning of the stack (the spectrum of its lowest natural frequencies) corresponds with the frequency spectrum of excitation due to seismic effects. In this study, the SFSI system is modelled using finite element method and computations are carried out using program SASSI 2000. A parametric study is also carried out to understand the various factors affecting the SFSI and the seismic response of the stack. Results of the parametric analysis are expressed in terms of the dynamic stiffness and damping factors, spectral ratio, response spectrum of acceleration, response spectrum of relative displacement and peak acceleration at different heights of the stack. The calculated responses are interpreted in light of differences between the idealized system and the real physical situation. The site conditions such as relative stiffness of the layers (shear wave velocity ratio), depth of layers over half-space and embedment ratio are the important factors influencing the SFSI effects on the seismic response of the stack.